Fuzzy logic and pi controller for photovoltaic panel battery charging system - Motakabber, S. M. A.; Zahirul Alam, A. H. M.; Mazbahur, Rahman Khan; Syed Ahmad, Fawwaz Wafa (IIUM Press, 2022)
Due to the nonlinear property of the PV panels, there are a few significant restrictions and limitations in the PV solar system. The PV panels always have to depend on environmental conditions such as temperature and solar radiation to generate efficient power. This paper proposed an optimum control system that can handle the uncertainties and nonlinearities of any system by using the Fuzzy Logic Control system (FLC). The proposed system utilized an FLC system for a DC-DC boost converter, tracking the PV panel’s maximum power point (MPPT). A PI control system is also used to maintain the continuous power supply for an optimum battery charging system for the DC-DC Buck converter. The goal is to provide constant voltage and appropriate current for charging the battery. It will increase the system efficiency and reduce the losses. It would also increase the battery life cycle and help the battery to charge fast. There are several MPPT methods found in the literature. The FLC can make a precise decision by considering the environmental state of the system. It can get a response to nonlinear environmental conditions instantly. The proposed system yielded an expected accuracy of 92% to 96%, with a system efficiency of 76% to 83%. Besides, it does not require any knowledge about the system, since it is a rule-based system. The entire system has been designed in MATLAB/Simulink. The simulation results have been analyzed under 9 environmental states in a 1.0 s period.